1997
DOI: 10.1097/00007890-199704270-00002
|View full text |Cite
|
Sign up to set email alerts
|

T-Cell Costimulatory Blockade in Experimental Chronic Cardiac Allograft Rejection

Abstract: Chronic rejection is a T cell-dependent process and blockade of the CD28-B7 T-cell costimulatory activation pathway by the fusion protein CTLA4Ig has been shown to prevent the development of accelerated graft arteriosclerosis in a rat model of chronic cardiac allograft rejection. The effectiveness of T-cell costimulatory blockade at preventing chronic allograft rejection in a clinically relevant model in combination with cyclosporine therapy has not been investigated. Using the well-established LEW into F334 h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
24
0

Year Published

1998
1998
2015
2015

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 58 publications
(25 citation statements)
references
References 39 publications
1
24
0
Order By: Relevance
“…They also noted that the increased capillary density was associated with T cell and monocyte infiltrates within the parenchyma of cardiac transplants (113). Using an established Lewis into Fisher rat model of chronic cardiac allograft rejection (8,114,115), we also found that angiogenesis was present in large CAV lesions, again in association with mononuclear infiltrates. Because the neovascular response itself is proinflammatory, we questioned whether it could sustain the growth of the intimal component of the CAV lesion.…”
Section: Angiogenesis and Chronic Allograft Rejectionsupporting
confidence: 52%
“…They also noted that the increased capillary density was associated with T cell and monocyte infiltrates within the parenchyma of cardiac transplants (113). Using an established Lewis into Fisher rat model of chronic cardiac allograft rejection (8,114,115), we also found that angiogenesis was present in large CAV lesions, again in association with mononuclear infiltrates. Because the neovascular response itself is proinflammatory, we questioned whether it could sustain the growth of the intimal component of the CAV lesion.…”
Section: Angiogenesis and Chronic Allograft Rejectionsupporting
confidence: 52%
“…In particular, blocking T cell-costimulatory activation early after transplantation prevents development of experimental chronic cardiac (9)(10)(11), as well as renal (12), allograft rejection. It has been suggested, however, that continuous T cell recognition of alloantigen, presumably via the indirect pathway (i.e., T cells that recognize donor-derived peptides presented by self antigen-presenting cells [APCs] 1 ), and activation may play an important role in progression of chronic rejection (13), although definitive studies are lacking. Understanding these mechanisms is essential for development of clinical strategies to prevent and interrupt progression of chronic allograft rejection.…”
Section: Introductionmentioning
confidence: 99%
“…Signal 2, a costimulatory signal, is delivered by interaction of T cell receptors with their specific ligands on APCs. Perhaps the best characterized T cell-costimulatory signal is that delivered by CD28 binding to B7 (13,(17)(18)(19)(20); blockade of this pathway prevents acute graft rejection and induces tolerance in some transplant models (13,(21)(22)(23)(24)(25)(26)(27). More recently, we have shown that early blockade of CD28-B7 by CTLA4Ig prevents development of chronic rejection (9,12).…”
Section: Introductionmentioning
confidence: 99%
“…We need to explore whether CTLA4Ig may be used safely and effectively with other immunosuppressive agents or agents that block other costimulatory pathways, such as the CD40/CD154 pathway (24)(25)(26). Indeed, there are experimental data in small animals to indicate that calcineurin inhibitors, such as cyclosporine, may abrogate the immunosuppressive or tolerogenic effects of B7 and/or CD154 blockade (24,27,28). Finally, we need to investigate and better understand the exact mechanisms of costimulatory blockade in vivo in humans with different diseases and to develop surrogate markers to monitor disease activity and response to therapy.…”
Section: Figurementioning
confidence: 99%